Effect of Exercise on Motor and Nonmotor Symptoms of Parkinson's Disease - Dashtipour, Khashayar (Parkinsons Dis, 2015)
Background. Novel rehabilitation strategies have demonstrated potential benefits for motor and non-motor symptoms of Parkinson's disease (PD). Objective. To compare the effects of Lee Silverman Voice Therapy BIG (LSVT BIG therapy) versus a general exercise program (combined treadmill plus seated trunk and limb exercises) on motor and non-motor symptoms of PD. Methods. Eleven patients with early-mid stage PD participated in the prospective, double-blinded, randomized clinical trial. Both groups received 16 one-hour supervised training sessions over 4 weeks. Outcome measures included the Unified Parkinson's Disease Rating Scale (UPDRS), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI) and Modified Fatigue Impact Scale (MFIS). Five patients performed general exercise and six patients performed LSVT BIG therapy. Post-intervention evaluations were conducted at weeks 4, 12 and 24. Results. The combined cohort made improvements at all follow-up evaluations with statistical significance for UPDRS total and motor, BDI, and MFIS (P < 0.05). Conclusion. This study demonstrated positive effects of general exercise and LSVT BIG therapy on motor and non-motor symptoms of patients with PD. Our results suggest that general exercise may be as effective as LSVT BIG therapy on symptoms of PD for patients not able to readily access outpatient LSVT BIG therapy.